THE ROLE OF POLICE PERSONNEL IN BANK SECURITY AS A CERTAIN VITAL OBJECT IN MAINTAINING STATE ASSETS AND THREATS TO SECURITY DISORDERS IN THE LAW OF THE SOUTH ACEH POLRES - Arianto, Khusmaidi; Marlina, Marlina; Purba, Nelvita (LPPM YPITI, 2021)
In the midst of the escalation of security threats to vital objects, both Obvitnas and certain vital objects, precisely the security forces placed at each bank as certain vital objects are security units (Security Guard). Of course this is not in accordance with the implementation of the main tasks of the National Police in maintaining public order and security. The reality, it can be seen that most of the banking institutions are guarded by the Security Unit (Security Guard). The problem in this research is how is the authority arrangement of the National Police personnel in securing the Bank as a certain vital object? What is the role of Southeast Aceh Regional Police personnel in securing banks as certain vital objects in the Southeast Aceh Regional Police? What are the obstacles in the implementation of the role of South Aceh Regional Police personnel in securing banks as certain vital objects in the South Aceh Regional Police? This type of research is empirical juridical research, while the nature of the study is descriptive analysis. This research uses several approaches, namely the law and conceptual approach. The research data consisted of primary and secondary data sources. The data analysis used in this study is qualitative data analysis. Based on the results of the study, the organizer of securing the Bank as a certain vital object becomes the authority of the Regional Police Chief or is at the Regional Police level (in this case the Aceh Regional Police). Southeast Aceh Regional Police, do not have the authority to provide security services and/or provide security management system services to banks as managers of certain vital objects. Aceh Tenggara Police officers as members of the National Police in the jurisdiction of the Aceh Regional Police can be placed at certain banks to provide security services. Obstacles in the implementation of the role of personnel of the Southeast Aceh Regional Police in securing banks as certain vital objects in the Southeast Aceh Regional Police, which lie in the legal substance, legal structure and legal culture.